Prevalence of depression and its associated factors among stroke survivors in Saudi Arabia. Issue 3 (20th October 2022) - Abuadas, Fuad H.; Ayasrah, Shahnaz M.; Ahmad, Muayyad M.; Abu‐Snieneh, Hana M.; Obiedallah, Hayyaf F.; Basheti, Iman A.
Abstract: Aim: The purpose of this study was to investigate the prevalence of poststroke depression (PSD) in Saudi Arabia and its association with socio‐demographic and clinical factors. Design: A predictive correlational cross‐sectional study. Methods: The study adopted a non‐probability convenience sampling method to recruit 211 stroke survivors between April and October 2021 from the neurology outpatient departments of two main governmental hospitals in Saudi Arabia. PSD was measured using a self‐assessment reliable and valid scale (The Hospital Anxiety and Depression Scale [HADS]). Results: More than two‐thirds (70.6%) of the study sample (Mean age = 53 years, SD = 8.5, 51.2% were males) experienced some degree of depression (Score ≥8); of these, approximately half (48.8%) were in severe depression. The final prediction model was statistically significant (χ2 [15] = 31.39, p  ˂ .01). PSD is a statistically significant health issue and requires immediate attention by healthcare providers to improve the health outcomes of stroke survivors.